Parenting of Parents To Building A Child Memorizing The Qur'an - Martina Ayu Wulandari; Nur Naria Dina Ramadhan (Educan : Jurnal Pendidikan Islam, 2021)
Family is the first education for a child, before school and the surrounding environment. However, education in the family is currently far from what is expected, one of which is that many parents do not care about the educational development of their children, especially in providing motivation and getting closer to the Qur'an. This study aims to describe the types, methods and results of parenting to foster children who memorize the Qur'an. The results of this study indicate that: (1) The type of parenting style of parents to foster children who memorize the Qur'an is authoritarian, permissive, and democratic, (2) Ways of parents to foster children who memorize the Qur'an include: Frequently reading the Qur'an since in the womb, Listening to murottal every time, Helping children muroja'ah every morning at dawn with disima' by parents, Helping children recite the Koran and deposit memorization every evening at dusk to parents, Choosing a good school that supports memorization programs Al-Qur'an. Other aspects such as: praying to Allah, Provide halal food and drinks, provide examples of good attitudes, behavior, and etiquette, and prevent children from television and programs that are not good to watch, (3) the results of authoritarian parenting can help children memorize 1 juz Al -Qur'an within 40 days, permissive within 3-4 months, while democratic within 40-50 days.